2001
DOI: 10.1093/sw/46.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Parenting for Families Living with HIV/AIDS

Abstract: Given the continual rise of HIV infection in our communities and the improved life span for many who are HIV-positive, social workers in all fields of practice have clients whose lives have been touched by HIV/AIDS. This article reviews relevant literature and reports on the parenting needs that emerged in a Canadian study that examined the experiences of 105 mothers and fathers living with HIV/AIDS. The majority of the children in the study were not HIV-positive. Some themes related to parenting in the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
13

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 21 publications
0
46
0
13
Order By: Relevance
“…In addition to the child's disease-stricken state and risk of mortality, HIV poses considerable challenges to the family caregivers (Antle et al, 2001;Potterton, 2007). A family caregiver can be defined as anyone who is an unpaid family member, a parent, sibling extended family member or recognized guardian involved in providing any type of physical and/or emotional care for an ill or disabled individual at home (Family Care Giver Alliance [FCA], 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the child's disease-stricken state and risk of mortality, HIV poses considerable challenges to the family caregivers (Antle et al, 2001;Potterton, 2007). A family caregiver can be defined as anyone who is an unpaid family member, a parent, sibling extended family member or recognized guardian involved in providing any type of physical and/or emotional care for an ill or disabled individual at home (Family Care Giver Alliance [FCA], 2012).…”
mentioning
confidence: 99%
“…Several concerns for the caregivers include feelings of helplessness, guilt and their poor socio-economic status even if their stress decreases when the child's health improves due to their treatment (Antle et al, 2001;Potterton, 2007;Bejane, 2013). Another important fact which exacerbates the level of stress for the child's biological parents is, in the majority of cases, the biological parents also are diagnosed with HIV and are dealing with their own treatment.…”
mentioning
confidence: 99%
“…Living with a stigmatizing and chronic terminal illness, seropositive mothers must grapple with the difficult decision of whether and when to inform their children about their diagnosis, weighing the potential benefits and costs associated with disclosure (e.g., Antle et al, 2001). Various rates of disclosure of parental HIV/AIDS to children have been reported, ranging from 0% (Esposito et al, 1999) to 74% (Armistead et al, 1997(Armistead et al, , 2001Bauman et al, Camacho et al, 2002;Forsyth et al, 1996;Lee & Rotheram-Borus, 2002;Murphy et al, 2001;Murphy, Marelich et al, 2002;Nagler et al, 1995;Niebuhr et al, 1994;Nostlinger et al, 2004;Ostrom et al, 2006;Pilowsky et al, 1999;Rotheram-Borus et al, 1997;Schrimshaw & Siegel, 2002;Shaffer et al, 2001;Sowell et al, 1997;Tompkins et al, 1999;Wiener et al, 1998), and likely depend on such factors as child age, disease progression, quality of the parent-child relationship, and general cultural influences on disclosure-and child-related beliefs.…”
mentioning
confidence: 99%
“…In support of this proposal, a study by Save the Children (2002) also advocates that teachers need to educate themselves on the effects HIV/ AIDS and poverty have on children, in an attempt to minimise discrimination in schools and the wider community. A study by Antle, Wells, Goldie, DeMatteo and King (2001) furthermore supports this idea, suggesting that schools and teachers (amongst other service providers) ought to be trained in terms of the potential effects of HIV/AIDS on families, advocating that schools need to be transformed into safe places where community members can disclose their status. We argue that the teachers in this study showed that with minimal intervention they can take small but confident steps to assist a community -a community which should include their pupils.…”
Section: S108mentioning
confidence: 97%